Tectonomagmatic evolution of the final stages of rifting along the deep conjugate Australian‐Antarctic magma‐poor rifted margins: Constraints from seismic observations. Issue 4 (24th April 2015) - Gillard, Morgane; Autin, Julia; Manatschal, Gianreto; Sauter, Daniel; Munschy, Marc; Schaming, Marc
Abstract The processes related to hyperextension, exhumed mantle domains, lithospheric breakup, and formation of first unequivocal oceanic crust at magma‐poor rifted margins are yet poorly understood. In this paper, we try to bring new constraints and new ideas about these latest deformation stages by studying the most distal Australian‐Antarctic rifted margins. We propose a new interpretation, linking the sedimentary architectures to the nature and type of basement units, including hyperextended crust, exhumed mantle, embryonic, and steady state oceanic crusts. One major implication of our study is that terms like prerift, synrift, and postrift cannot be used in such polyphase settings, which also invalidates the concept of breakup unconformity. Integration and correlation of all available data, particular seismic and potential field data, allows us to propose a new model to explain the evolution of magma‐poor distal rifted margins involving multiple and complex detachment systems. We propose that lithospheric breakup occurs after a phase of proto‐oceanic crust formation, associated with a substantial magma supply. First steady state oceanic crust may therefore not have been emplaced before ~53.3 Ma corresponding to magnetic anomaly C24. Observations of magma amount and its distribution along the margins highlight a close magma‐fault relationship during the development of these margins.